Reliability and Validity of an Instrument that Measures Entrepreneurship (Revista científica Pensamiento y Gestión, 2020)
The process that goes from prospective decisions (oriented to risks ofmaximum profits with respect to minimum insurance benefits) to deliberateactions (oriented by avoidance of failures, based on the systematizationof errors and successes) is addressed in the present work, aiming to specifya model for the study of Internet entrepreneurship. A non-experimentalstudy was carried out with a non-probabilistic selection of 135 entrepreneurs.From a structural model, the reflective factor of the construct wasfound to be deliberate actions, but such findings are only applicable to thesample since the type of study, sampling, and statistical analysis suggestthe contrast of the model in other scenarios would increase the percentageof the explained variance of its factors, that added to 57% in this case.